Effects of vineyard inter-row management on the diversity and abundance of plants and surface-dwelling invertebrates in Central Romania - Cristina Fiera; Werner Ulrich; Daniela Popescu; Claudiu-Ioan Bunea; Minodora Manu; Ioana Nae; Melania Stan; Bálint Markó; István Urák; Andrei Giurginca; Nicole Penke; Silvia Winter; et al. (Journal of Insect Conservation, 2020)
Vineyard inter-rows are important biodiversity hotspots within agricultural landscapes, especially when they are covered with vegetation. However, little is known on the effects to management intensity on a broad range of surface-dwelling invertebrates and their interaction with vegetation. We assessed the diversity and activity density of ants, beetles, millipedes, mites, spiders, springtails and woodlice using pitfall traps in vineyards with either high management intensity (HI) consisting of frequently tilled inter-rows or low management intensity (LO) with alternating tillage in every second inter-row. The study was performed in the Târnave wine region in Central Romania. We wanted to know whether, (i) vineyard management intensity affects the diversity of plants and invertebrates, and (ii) local habitat characteristics affect species richness of different functional guilds and taxa. Species richness of some invertebrate taxa (Coleoptera, Araneae, Formicidae) did significantly differ between HI and LO vineyards. Only phytophages (some Coleoptera) increased in species richness and activity density with vegetation cover. Vineyard soil properties (organic matter content, pH, P, and K) did not significantly differ between HI and LO vineyards. We conclude that vineyard inter-row management can affect both the conservation of biodiversity and the provision of biodiversity-driven ecosystem services.